Padmanabhapuram Palace-An Aesthetic Architecture Of Venadu - Asha, U.; Jeeva, R. Christal (Journal of Neonatal Surgery, 2025)
Padmanabhapuram Palace is a remarkable 16th Century wood palace of the erstwhile Venadu Kingdom now in the State of Tamil Nadu. Replete with intricate wood carvings and ornate murals, the Palace is an exceptional example of indigenous building techniques based on the science of carpentry and craftsmanship in wood. Padmanabhapuram Palace, has a style unparalleled in historic building systems which is unique to this region. Padmanabhapuram Palace is the oldest, largest and well-preserved surviving example representative of the traditional wooden architecture in India. The Palace is a product of the fusion of traditional building technology, exquisite craftsmanship and superior knowledge of material science. The Palace bears living testimony of traditional timber architecture with strict adherence to the traditional building code of the Tamil culture which has clear prescription for every aspect of the function and placement of a structure, direction, size and design, including specifications for the layout of designated spaces within individual structures.